The development of a way to evaluate sugar intake in Japan - Takada, Yuri; Kobayashi, Minatsu (International Journal of Human Culture Studies, 2013)
In recent years mainly in the United States, the influence of excessive fructose intake on health has been reported. Although in the 2010 Japanese dietary intake reference, a warning against excessive fructose intake was published for the first time, there is insufficient evidence of its harmful effects. It is difficult to estimate sugar intake because the Japanese food composition table contains no descriptions about the components of sugars. Therefore in this research, we tried to develop a new table in order to overcome this difficulty.The amounts of galactose, glucose, fructose, lactose, sucrose, and maltose are detailed in the United States Department of Agriculture Food Composition Table (USDA_FCT). The Japanese table (J_FCT) also uses this data. Regarding foods like for example “dorayaki” which is a traditional Japanese sweet sponge cake filled with bean jam, if its ingredients contained more than 10g of sugar per 100g, it was listed in the table.In total, the sugar content of 557 foods was listed in the new J_FCT using the data from USDA_FCT. In fact, we were able to list the majority of its high sugar content foods in the J_FCT. As a result of the present study, estimations of Japanese sugar intake and investigation into the links between sugar intake and risk of disease, can be carried out using this new sugar FCT.